In-Fiber Optic Salinity Sensing: A Potential Application for Offshore Concrete Structure Protection - Luo, D.; Li, P.; Yue, Y.C.; Ma, J.X.; Yang, H.Z. (MDPI, 2017)
The protection of concrete structures against corrosion in marine environments has always been a challenge due to the presence of a saline solution—A natural corrosive agent to the concrete paste and steel reinforcements. The concentration of salt is a key parameter influencing the rate of corrosion. In this paper, we propose an optical fiber-based salinity sensor based on bundled multimode plastic optical fiber (POF) as a sensor probe and a concave mirror as a reflector in conjunction with an intensity modulation technique. A refractive index (RI) sensing approach is analytically investigated and the findings are in agreement with the experimental results. A maximum sensitivity of 14,847.486/RIU can be achieved at RI = 1.3525. The proposed technique is suitable for in situ measurement and monitoring of salinity in liquid.